3(x-1)=-24

Simple and best practice solution for 3(x-1)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)=-24 equation:


Simplifying
3(x + -1) = -24

Reorder the terms:
3(-1 + x) = -24
(-1 * 3 + x * 3) = -24
(-3 + 3x) = -24

Solving
-3 + 3x = -24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3x = -24 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = -24 + 3
3x = -24 + 3

Combine like terms: -24 + 3 = -21
3x = -21

Divide each side by '3'.
x = -7

Simplifying
x = -7

See similar equations:

| (49-3x)=(34-2x) | | 49-3x=34-2x | | 1.3x+-13=-5.2 | | 2c+4+3c=-36 | | 5x+15=22 | | 49-3x=3x-5 | | 7x-28=-14 | | 4(x+2)+x-11=2x-3+3(x+4) | | -3(9c+8)=26 | | (A+2)0.78=3.9 | | 4(90-x)+2=(180-x)+8 | | C=X^2-15x+50 | | 3(x+5)=x-10 | | 3535x-5725x+58y=4734z | | a/4-3/4=1/3 | | y^2-12y+27= | | X^5-4x^4+7x^3-10x^2+10x-4=0 | | A=(7x)(3x) | | -7x-3=13 | | 9.5=0.4(5x)+2.5 | | 9x+1=5x+15 | | 7*y-3=2*y-3 | | x^2-10x+25=x^2-8x+16+1 | | (x-5)=(x-4) | | 10(2x-10)=0 | | 3*200=2+x | | ln(x+8)-ln(x-2)=ln(x+2) | | h=-16t^2+250 | | a-1=14 | | 2x-5=8x+7-4x | | 4(2z+1)-6=70 | | x^2-10x+25-1=0 |

Equations solver categories